"But I think there's always been that stigma": Adult women's perceptions of menstrual product advertising. Issue 5 (4th May 2023) - Mucedola, Adriana S.; Smith, Andrea M.
Abstract: The global value of the menstrual product market recently surpassed 40 billion dollars, yet little attention has been paid to how menstrual product advertising may impact women's perceptions of menstruation. We interviewed a diverse cohort of 18 adult women to understand how menstrual product advertising shapes women's interpretations of their bodies and the menstrual process. Three themes emerged, including gendered stigmatization, depictions of hyper-feminine women, and false narratives about periods. We concluded that dominant patriarchal images of women on their periods persist in female-targeted advertising and offer solutions for advertisers to eliminate stigmas and encompass inclusivity.